The wolves of Wall Street? Managerial attributes and bank risk - Hagendorff, Jens; Saunders, Anthony; Steffen, Sascha; Vallascas, Francesco (Journal of Financial Intermediation, 2021)
We find that chief executive officers and chief financial officers exert significant individual effects on bank risk. Manager transitions, including transitions generated by plausibly exogenous manager departures, lead to abnormally large changes in bank risk. We demonstrate that the effects of managers on bank risk are sizable and manager-specific. The effects are also partly anticipated by the board because they are reflected in managers’ pay. However, wide-ranging personal attributes, including biographical, experience, and compensation data, only explain a small share of managers’ impact on bank risk. This implies that attempts to rein in bank risk-taking by targeting manager characteristics will be challenging for investors and regulators.